APPLICATION OF PERSONAL PROTECTIVE EQUIPMENT AS THE WORK SAFETY PROCEDURE IN THE WELDING PROCESS - Sunarji; Rachmasari Pramita Wardhani (Mechanical Engineering Departement - Universitas Tridharma, 2021)
PPE is defined in the Regulations as: